Which frequency is better for pediatric shock wave lithotripsy? Low intermediate or high: A systematic review and meta-analysis - Xiao, Kaiwen; Zhou, Liang; Zhu, Shiyu; Lin, Lede; Di, Xingpeng; Li, Hong (Frontiers in Surgery, 2023)
Background: To explore the optimal frequency for pediatric extracorporeal shock wave lithotripsy (ESWL) in the treatment of upper urinary stones. Methods: A systematic literature search was undertaken using PubMed, Embase, Web of Science and Cochrane Central Register of Controlled Trials databases to identify eligible studies published before January 2023. Primary outcomes were perioperative efficacy parameters, including ESWL time, anesthesia time for ESWL sessions, success rates after each session, additional interventions needed, and treatment sessions per patient. Secondary outcomes were postoperative complications and efficiency quotient. Results: Four controlled studies involving 263 pediatric patients were enrolled in our meta-analysis. In the comparison between the low-frequency and intermediate-frequency groups, we observed no significant difference as regards anesthesia time for ESWL session (WMD=-4.98, 95% CI -21.55~11.58, p=0.56), success rates after ESWL sessions (first session: OR=0.02 95%CI -0.12~0.17, p=0.74; second session: OR=1.04 95%CI 0.56~1.90, p=0.91; third session: OR=1.62 95%CI 0.73~3.60, p=0.24), treatment sessions needed (WMD=0.08 95%CI -0.21~0.36, p=0.60), additional interventions after ESWL (OR=0.99 95%CI 0.40~2.47, p=0.99) and rates of Clavien grade 2 complications (OR=0.92 95%CI 0.18~4.69, p=0.92). However, the intermediate-frequency group may exhibit potential benefits in Clavien grade 1 complications. In the comparison between intermediate-frequency and high-frequency, the eligible studies exhibited higher success rates in the intermediate-frequency group after the first session, the second session and the third session. More sessions may be required in the high-frequency group. With respect to other perioperative, postoperative parameters and major complications, the results were similar. Conclusions: Intermediate-frequency and low-frequency had similar success rates and seemed to be the optimal frequency for pediatric ESWL. Nevertheless, future large-volume, well-designed RCTs are awaited to confirm and update the findings of this analysis.